Population dynamics, pathogen detection and insecticide resistance of mosquito and sand fly in refugee camps, Greece - Emmanouil Alexandros Fotakis; Ioannis Apostolou Giantsis; Javier Castells Sierra; Filianna Tanti; Sofia Balaska; Konstantinos Mavridis; Sofoklis Kourtidis; John Vontas; Alexandra Chaskopoulou (BMC, 2020)
Abstract Background As of 2015 thousands of refugees are being hosted in temporary refugee camps in Greece. Displaced populations, travelling and living under poor conditions with limited access to healthcare are at a high risk of exposure to vector borne disease (VBD). This study sought to evaluate the risk for VBD transmission within refugee camps in Greece by analyzing the mosquito and sand fly populations present, in light of designing effective and efficient context specific vector and disease control programs. Methods A vector/pathogen surveillance network targeting mosquitoes and sand flies was deployed in four temporary refugee camps in Greece. Sample collections were conducted bi-weekly during June-September 2017 with the use of Centers for Disease Control (CDC) light traps and oviposition traps. Using conventional and molecular diagnostic tools we investigated the mosquito/sand fly species composition, population dynamics, pathogen infection rates, and insecticide resistance status in the major vector species. Results Important disease vectors including Anopheles sacharovi, Culex pipiens, Aedes albopictus and the Leishmania vectors Phlebotomus neglectus, P. perfiliewi and P. tobbi were recorded in the study refugee camps. No mosquito pathogens (Plasmodium parasites, flaviviruses) were detected in the analysed samples yet high sand fly Leishmania infection rates are reported. Culex pipiens mosquitoes displayed relatively high knock down resistance (kdr) mutation allelic frequencies (ranging from 41.0 to 63.3%) while kdr mutations were also detected in Ae. albopictus populations, but not in Anopheles and sand fly specimens. No diflubenzuron (DFB) mutations were detected in any of the mosquito species analysed. Conclusions Important disease vectors and pathogens in vectors (Leishmania spp.) were recorded in the refugee camps indicating a situational risk factor for disease transmission. The Cx. pipiens and Ae. albopictus kdr mutation frequencies recorded pose a potential threat against the effectiveness of pyrethroid insecticides in these settings. In contrast, pyrethroids appear suitable for the control of Anopheles mosquitoes and sand flies and DFB for Cx. pipiens and Ae. albopictus larvicide applications. Targeted actions ensuring adequate living conditions and the establishment of integrated vector-borne disease surveillance programs in refugee settlements are essential for protecting refugee populations against VBDs.